Predicting social skills in disadvantaged Chinese high school students through physical education - Primo, Laura; González-Hernández, Juan; Yang, Yin; López de Subijana, Cristina (Frontiers in Psychology, 2023)
Introduction This study analyzed the relationships between social skills and motivation to Physical Education, students´ perceived support regarding Physical Education lessons (from parents, teachers and peers) and basic needs satisfaction in a sample of disadvantaged high school Chinese students according to Self-Determination Theory-related main principles. Physical Education classes are a great opportunity to develop not only psychomotor and physiologically, but also psychosocially in young people, and that is why this study investigates the relationship between the social skills of the students and these other main variables of the Self-Determination Theory. Methods Two hundred and nine disadvantaged students enrolled in a camp organized by a non-governmental organization in Chengdu province (15.9 ± 0.83 years; 73.9% female and 26.1% male) completed the Chinese versions of the following Self-Determination Theory-related questionnaires (independent variables): Learning Climate Questionnaire, Activity- Feeling States Scale, Perceived Locus of Causality scale; and social skills questionnaire (dependent variable): Matson Evaluation of Social Skills with Youngsters Scale. Results The standard multiple regression model to predict social skills based on perceived support, basic needs satisfaction and motivation towards Physical Education was significant (F(11, 195)= 13.85; p < .001; R2=.44; Cohen’s f2= 0.78). The social skills of the students were positively related to peer support and relatedness subscales. In contrast, introjected regulation, external regulation, and amotivation were adversely correlated with social skills. Discussion We believe that this information would help policymakers and teachers design new policies, actions, and teaching methodologies to implement for the development of Physical Education and sport programs in China, those that will help young people throughout their life span.